Longitudinal relationships between polycyclic aromatic hydrocarbons exposure and heart rate variability: Exploring the role of transforming growth factor-β in a general Chinese population - Ma, Jixuan; Tan, Qiyou; Nie, Xiuquan; Zhou, Min; Wang, Bin; Wang, Xing; Cheng, Man; Ye, Zi; Xie, Yujia; Wang, Dongming; Chen, Weihong (Journal of hazardous materials, 2022)
We aim to investigate the long-term adverse effects of polycyclic aromatic hydrocarbons (PAHs) exposure on heart rate variability (HRV) reduction, and to assess the potential role of transforming growth factor-β1 (TGF-β1) in such relationship. We enrolled 2985 adult residents with 4100 observations who participated at baseline and 6-years follow-up from Wuhan-Zhuhai cohort. Ten detectable urinary PAHs metabolites and two HRV indices were repeatedly measured at baseline and follow-up; and plasma TGF-β1 levels were also determined for all subjects. We observed that both total urinary low molecular weight PAHs (ΣLWM OH-PAH) and total urinary high molecular weight PAHs (ΣHWM OH-PAH) were negatively associated with HRV reductions (P < 0.05). Subjects with persistent high levels of ΣHWM OH-PAH had a significant reduction in HRV over 6 years, and the incensement of TGF-β1 could aggravate above adverse effects in a dose-response manner. All kinds of PAHs were positively associated with plasma TGF-β1 elevation, which in turn, were negatively related to HRV indices. Increased TGF-β1 significant mediated 1.34–3.62% of PAHs-associated HRV reduction. Our findings demonstrated that long-term high levels of PAHs exposure could cause HRV reductions, and TGF-β1 may play an essential role in such association. [Display omitted] •Long-term exposure of PAHs may cause HRV reductions over 6 years.•TGF-β1 aggravate HRV reductions caused by PAHs exposure over 6 years.•TGF-β1 may be a possible mechanism underlying the reduction of HRV caused by PAHs.